IMPLEMENTASI BUILDING INFORMATION MODELING 4D SEBAGAI PROJECT CONTROL PEMBANGUNAN GEDUNG 3 LANTAI (Jurnal Rekayasa dan Aplikasi Teknik Sipil, 2024)
The construction industry is rapidly evolving with complex work items, creating challenges in maintaining the completion of tasks according to the planned schedule. Detailed supervision is crucial to ensure the project proceeds according to the scheduling plan. This research focuses on developing the concept of Building Information Modeling 4 Dimensions (BIM 4D) in the process of controlling progress on a 3-story building construction project. The research begins with collecting data such as working drawings, the Bill of Quantities (BoQ), and the S-curve. The process starts with identifying the schedule, creating a Work Breakdown Structure (WBS) to determine the sequence of tasks, making a list of relationships between work activities, rescheduling using scheduling software to obtain a schedule in the form of a Gantt chart, and integrating the 3D model and Gantt chart through BIM 4D. The results of the study provide a visual sequence and weight of tasks with a planning schedule of 194 days. There is a difference of 24 days between the BIM 4D simulation and the schedule based on the S-curve.